Hybrid free space optics/radio frequency communication for next generation wireless networks - Sharma, Shubha (Nanyang Technological University, 2021)
Free space optical (FSO) communication is a point to point transmission using laser beams that supports high data rate (up to GBPS) for short range transmission up to few kilometers. However, the FSO link is highly susceptible to atmospheric effects like pressure and temperature, which cause atmospheric turbulence along the propagation path. Attenuation due to fog, misalignment, and pointing errors are other major factors, which can cause FSO link failure. These factors lead to the variation in laser beam strength at the receiver that affects the link range and the system reliability. Therefore, to improve the performance of FSO links, it is wise to backup with reliable millimeter-wave (MMW) radio frequency (RF) links. Meanwhile, the FSO and MMW/RF channels exhibit complementary characteristics to atmospheric and weather conditions. Specifi cally, the performance of FSO link deteriorates signi ficantly due to fog. However, it is not sensitive to rain. On the contrary, the performance of MMW RF link degrades due to rain, but is not sensitive to fog. Therefore, these two complementary characteristics paved the way for hybrid FSO/MMW RF communication, which provides reliable high data rate transmission. For a next generation cellular backhaul architecture, by utilizing both FSO and MMW RF technologies and incorporating cooperative diversity using a relay node, the performance and coverage area of the FSO communication system can be signifi cantly improved. In this work, to counteract the adverse effects of the FSO link, a reliable MMW/RF link is used as a backup. A novel switching scheme for hybrid FSO/RF system considering a cooperative decode-and-forward (DF) relay network is proposed. Speci fically, the system consists of FSO and RF sub-systems, where FSO sub-system has the priority to transmit and RF sub-system serves as a back up when the FSO sub-system is in outage. The exact outage probability, average symbol error rate (SER) and ergodic capacity expressions are derived for cooperative DF relay network with and without a direct link. For the scenario with direct link, maximal ratio combining (MRC) and selection combining (SC) schemes are assumed at the destination. In addition, the asymptotic outage, SER and ergodic capacity expressions with lower computational complexity are derived and the diversity order is determined. For the proposed system, the outage threshold signal-to-noise ratio (SNR) is an important parameter and the optimum value for the same has been calculated to achieve the target average SER and high capacity. The effect of pointing errors in the presence of Gamma-Gamma atmospheric fading together with path loss attenuation is further considered in this work. Transmit beam waist and detector radius are optimized to minimize the average SER and to maximize the capacity. To overcome the deterioration in the performance of the FSO link, multiple apertures/antennas are employed in the hybrid FSO/RF system, which are well known to counteract the adverse fading effects. This thesis presents a multiple-input-single-output (MISO) hybrid FSO/RF system with transmit aperture/antenna selection (TAS). The proposed system consists of a MISO FSO sub-system and MISO MMW RF sub-system with N transmit apertures and antennas, respectively. The MISO FSO sub-system is given higher priority to transmit using the selected best link. The aperture with the highest gain at the receiver is considered as the best link. The best link of the MISO MMW RF sub-system is used when the FSO sub-system is in outage. The FSO links are assumed to experience Malaga distributed turbulence induced fading together with pointing errors and path loss. The effect of pointing errors over the system performance is analyzed and the optimum value of transmit beam waist is determined. The MMW RF link is assumed to experience κ-μ shadowed fading. The probability density function (PDF) and cumulative distribution function (CDF) expressions of TAS-based MISO FSO and RF sub-systems are derived. These expressions are further utilized to derive the exact and asymptotic expressions for outage probability, average SER, and capacity for the proposed hybrid system. From the asymptotic average SER expressions, diversity order is determined. In context of multiple aperture/antenna-based hybrid FSO/RF system, the present work also investigates the performance of a space shift keying (SSK)-based multiple-input single-output (MISO) hybrid FSO/RF system. The proposed hybrid system considers an optical SSK (OSSK)-based FSO sub-system as a default transmission option with Nx1 apertures. The MMW RF link with M-ary pulse amplitude modulation (MPAM) signaling is utilized when FSO sub-system is in outage. Similar to the TAS hybrid FSO/RF system, the FSO links are modeled using Malaga distribution with pointing errors and the MMW RF link is modeled using κ-μ shadowed distribution. A unifi ed performance analysis is addressed and novel expressions for average bit error rate (BER) are obtained. The theoretical results presented in the above mentioned proposed schemes have been extensively validated by Monte-carlo simulations. The effect of atmospheric turbulence, pointing errors, and path loss over the system performance is analyzed extensively by varying the values of these parameters. The results show that the proposed switching scheme for cooperative hybrid FSO/RF system drastically improves the performance compared to that of single hop (SH) switching-based hybrid FSO/RF and cooperative FSO systems. Large coding gains are observed in case of optimum beam waist compared to any arbitrary beam waist to achieve the same performance. The diversity gain depends on atmospheric turbulence and pointing errors. For the TAS-based MISO hybrid FSO/RF system, the results show that the proposed hybrid FSO/RF system is more reliable compared to the individual MISO FSO system and achieves higher capacity compared to the MISO RF system. Here, the diversity gain of the proposed system is dependent on atmospheric turbulence, pointing errors and the number of apertures. Signifi cant performance improvement is also observed for the SSK-based hybrid FSO/RF system compared to the individual OSSK-based FSO sub-system.